COVID-19 : How Will European Banks Fare? - Aiyar, Shekhar; Dao, Mai Chi.; Jobst, Andreas A.; Mineshima, Aiko. (Washington, D.C. : International Monetary Fund, 2021)
This paper evaluates the impact of the crisis on European banks' capital under a range of macroeconomic scenarios, using granular data on the size and riskiness of sectoral exposures. The analysis incorporates the important role of pandemic-related policy support, including not only regulatory relief for banks, but also policies to support businesses and households, which act to shield the financial sector from the real economic shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet